221 Evaluation of stress and anxiety in a grimed population playing the role of victims in a live terrorist attack exercise. (24th April 2018) - Loeb, Thomas; Groizard, Charles; Ozguler, Anna; Fleischel, Catherine; Gauthier, Karine; Baer, Michel
Abstract : Introduction: Emergency Medical Services (EMS) organise simulation exercises in near real conditions. In this exercises, volunteers usually act as victims. We set up a large-scale simulation exercise. The scenario was a terrorist attack causing 153 victims. Victims were played by nurse students. The aim of our study was to evaluate if playing a role of victim could generate stress and anxiety. Methods: The exercise took place at night on September 26, 2016. Fifteen days after, a questionnaire was sent to nurse students who took part as victims. Descriptive results are given in percentages and averages. Result: 126 participants did answer (82.4%). The average age was 23 years and 86% were women. 20.7% considered themselves as anxious or very anxious and 5.9% reported poor or very poor sleep. Their roles were assigned to severely injured (30%), involved (25%), deceased (21%), moderately injured (14%) and hostages (10%). During terrorist attack, 56.9% found that they were in a uncomfortable situation. 85% of the participants considered the attack as fairly or very impressive and 79% were afraid at some point during the exercise. For those who were scared, half said that this fear remained after the end of the exercise. 21 participants felt necessary to have an interview with a psychologist. More than 23% of participants felt that this exercise had been fairly or very disruptive and would deny or hesitate to participate again in a similar exercise. Discussion: Acting as a simulated victim, in a hyper-realistic live exercise, generate stress, fear or anxiety. In order not protect from unnecessary stress, it is essential for organisers to take this in consideration and offer to those who play victims acceptable conditions of comfort. Further studies are required to recognise factors that cause a predisposition of stress in such situations and set aside those with risks.